Relationship between pitch volume and subjective report of injury in high school female fast-pitch softball pitchers - Gooch, B.; Lambert, B. S.; Goble, H.; McCulloch, P. C.; Hedt, C. (Sports Health: A Multidisciplinary Approach, 2021)
Background: The relationship between pitch volume and injury is well-represented within baseball literature. However, the impact of softball pitch volume on injury epidemiology is limited.